Cadmium(II) compounds of the bis-cyanoethyl derivative (LCX) of Me8[14]aneC (LC): characterization and antibacterial studies - Chakraborty, Avijit; Rabi, Saswata; Dey, Lucky; Palit, Debashis; Dey, Benu Kumar; Tiekink, Edward R. T. *; Roy, T. G. (Elsevier, 2022)
The isomeric ligand LC, a saturated analogue of 2,9-C-meso-Me8[14]diene, on reflux with excess acrylonitrile afforded 1,8-N-pendant cyanoethyl derivative LCX. Interaction of LCX with cadmium(II) perchlorate, nitrate, acetate, and chloride salts produced six coordinated octahedral compounds, [Cd(LCX) (ClO4)2]∙2H2O, [Cd(LCX) (NO3)2], [Cd(LCX) (CH3COO)2], and [Cd(LCX)Cl2], respectively. Further, axial substitution reactions between [Cd(LCX) (ClO4)2]∙2H2O and KI, KBr, KCl, KSCN, and NaNO2 in a 1:2 ratio yielded six coordinated octahedral compounds, [Cd(LCX)I2]∙H2O, [Cd(LCX)Br2]∙2H2O, [Cd(LCX)Cl(ClO4)]∙2H2O, [Cd(LCX) (NCS)2]∙H2O, and [Cd(LCX) (NO2) (ClO4)]∙2H2O, respectively. All of the newly prepared compounds have been characterized by analytical, spectroscopic, molar conductivity, and magnetochemical data. The crystal structure of the ligand LCX was determined by x-ray crystallography which showed the 14-membered ring to adopt an extended chair conformation. Antibacterial activities of the newly formed cadmium(II) complexes against selected bacteria showed these to exhibit moderate and selective activity with 1-4 and 8 exhibiting greatest potency against the gram negative bacterium Salmonella typhi, and 5, 6, and 7 against the gram positive bacterium Bacillus wiedmannii.